Recovery of zinc from metal-plating industrial wastewaters by liquid-liquid extraction - Sathityatiwat, Suthapat (2020)
The extraction of zinc(II) from zinc-plating wastewater by liquid-liquid extraction was studied using the commercial extractants di-(2-ethylhexyl)phosphoric acid (D2EHPA) and bis(2,4,4-trimethylpentyl)phosphinic acid (Cyanex® 272), as well as the ionic liquids, Trihexyltetradecylphosphonium bromide (Cyphos® 102), Trihexyltetradecylphosphonium decanoate (Cyphos® 103) and Trihexyltetradecylphosphonium bis(2,4,4- trimethylpentyl)phosphinate (Cyphos® 104), diluted in organic solvents. First, the commercial extractants and the ionic liquids with the most potential were selected based on the results from diluents, modifiers and stripping solution screening tests. Then, the optimization of extraction and re-extraction (stripping) conditions for each extractant was achieved either by effluent pretreatment (pH adjustment) to remove iron prior to liquid-liquid extraction or by adjusting the extractant-to-zinc ratio. Afterwards, one commercial extractant and one ionic liquid were selected for further evaluation based on the following parameters: reusability, contact time (kinetic studies), and loading capacity. Of the two commercial extractants, the most promising results were obtained with 20% (w/w) D2EHPA in kerosene and 3% (v/v) TBP (tributyl phosphate) as the modifier after a contact time of only five minutes. The extraction efficiency for zinc was 98%, with coextraction of iron which can be resolved by pre-treating the effluent to pH 5.5 to precipitate iron prior to liquid-liquid extraction. Selective stripping of zinc from the loaded organic phase was achieved using 0.6 M H2SO4. Under these optimized conditions, the reusability of the organic phase was successfully tested in three cycles of zinc extraction and re-extraction without loss of efficiency. Regarding ionic liquids, 0.08 M Cyphos® 102 in kerosene exhibited superior selectivity for zinc extraction (83%), with little to no co-extraction of iron. Despite this high efficiency, an issue of insolubility of Cyphos® 102 in the diluent was observed, with the ionic liquid being in a layer below kerosene. This insolubility issue made decantation difficult, which affected the reusability of the extraction system. However, the issue can be solved with the addition of 3% (v/v) decanol as modifier, but resulting in the decrease in zinc extraction efficiency to 40%. A raise of the concentration to 0.24 M Cyphos® 102 in kerosene with 3% (v/v) decanol allowed a 95% extraction efficiency of zinc with no insolubility being observed. On the other hand, the stripping of zinc from this loaded organic phase was obtained using a high concentration of HNO3 of 2M. Nevertheless, the problem of reusability of the organic phase remained, whereby zinc extraction decreased to 54% and re-extraction decreased to 5% in the second cycle. Therefore, time and effort need to be devoted to future studies to evaluate the application of Cyphos®102 in liquid-liquid extraction of zinc from zinc-plating wastewaters.